Survival and Evolution of CRISPR–Cas System in Prokaryotes and Its Applications - Shabbir, Muhammad Abu Bakr; Hao, Haihong; Shabbir, Muhammad Zubair; Hussain, Hafiz Iftikhar; Iqbal, Zahid; Ahmed, Saeed; Sattar, Adeel; Iqbal, Mujahid; Li, Jun; Yuan, Zonghui (Frontiers in Immunology, 2016)
Prokaryotes have developed numerous innate immune mechanisms in order to fend off bacteriophage or plasmid attack. One of these immune systems is Clustered regularly interspaced short palindromic repeats (CRISPR). CRISPR associated proteins play a key role in survival of prokaryotes against invaders, as these systems cleave DNA of foreign genetic elements. Beyond providing immunity, these systems have significant impact in altering the bacterial physiology in term of its virulence and pathogenicity, as well as evolution. Also, due to their diverse nature of functionality, cas9 endoribonuclease can be easily reprogrammed with the help of guide RNAs, showing unprecedented potential and significance for gene editing in treating genetic diseases. Here, we also discuss the use of NgAgo-gDNA system in genome editing of human cells.